Excess weight in preschoolers: prevalence and associated factors - Ilaine Schuch; Teresa G. de Castro; Francisco de A.G. de Vasconcelos; Carmem L.C. Dutra; Marcelo Z. Goldani (Jornal de Pediatria (Versão em Português), 2013)
Objective: To study the prevalence and factors associated with excess weight in children enrolled in public schools in the states of Rio Grande do Sul (RS) and Santa Catarina (SC). Methods: This was a cross-sectional study, carried out with children aged 4 to 6 years. The studied outcome was excess weight, defined by z-score > two standard deviations for body mass index (BMI)/age, compared with the World Health Organization (WHO) reference population of 2006/2007. Anthropometric measurements of body mass and height were measured in duplicate using standard techniques, in accordance with the WHO. Data were double entered using EPI-INFO software, release 6.04. Absolute and relative frequencies were calculated, as well as mean values and standard deviations. Associations between excess weight and other variables were assessed by using Poisson model with robust variance. STATA software release 12.0 was used (p < 0.05). Results: A total of 4,914 children were evaluated (2,578 in RS and 2,336 in SC). In RS, the incidence of excess weight was 14.4% (95% CI = 13.1% to 15.8%) and in SC, 7.5% (95% CI = 6.5% to 8.7%). The variables associated with excess weight were number of household members, maternal education, marital status, number of children, mother's age at birth of first child, gestational age, and birth weight. Conclusion: Children enrolled in public preschools in RS had a two-fold higher excess weight prevalence than that identified in SC, demonstrating a significant difference in the magnitude of childhood obesity in two Brazilian states located in the same region.